TOXICITY OF Aaptos suberitoides EXTRACT ON TIGER SHRIMP Penaeous monodon POST LARVAE - Rosmiati Rosmiati; Emma Suryati (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2014)
Marine sponges contain bioactive compounds which can be used not only for human diseases treatment but also for animal diseases treatment. Aaptos suberitoides has been reported to have potential as antibacterial against Vibrio harveyi in vitro. This study aims to study the toxicity effect of Aaptos suberitoides extract on tiger shrimp Penaeous monodon post larvae. The toxicity study of this extract was done by using soaking method. This experiment used Completely Randomized Design with 6 treatments of A.suberitoides extract namely A). 0 ppm, B). 31.3 ppm, C). 62.5 ppm, D). 125, E). 250 ppm, and F). 500 ppm. Each treatment consisted of 3 replications. Findings showed that A.suberitoides butanol extracts at the concentration up to125 ppm were safe for tiger shrimp post larvae. On the other hand, the higher concentration of that gave a toxic effect on the post larvae. The lowest mortality (20.0%) was obtained on the post larvae treated with butanol extract at the concentration of 31.3 ppm and the highest was found at the concentration of 500 ppm (97.0%). Compared to the negative control (0 ppm), there was no any difference exhibited by the post larvae treated with butanol extract at the concentrations of 31.3, 62.5, and 125 ppm. Beside that, these concentrations gave a normal growth and no abnormal behavior. The histological observation did not also show damage on post larvae haepatopancreas tissue.